Molecular and cellular mechanisms of the organogenesis and development of the mammalian carotid body. Issue 5 (30th December 2019) - Kameda, Yoko
Abstract: Despite significant advancements in understanding physiological properties of the carotid body, little attention has been paid to its organogenesis. This review addresses the molecular and cellular mechanisms underlying organogenesis of the carotid body in mammals. The carotid body consists of two types of cells, that is, glomus cells and sustentacular cells, that are derived from different origins. Glomus cells are derivatives of neural crest cells which form sympathetic ganglia. Sustentacular cells are derivatives of mesenchymal neural crest cells which colonize the third pharyngeal arch and form the wall of the third arch artery. Gene‐targeting studies indicate that three elements are required for carotid body organogenesis: the carotid sinus nerve (CSN), third arch artery, and superior cervical sympathetic ganglion (SCG). The CSN sends sensory fibers and Schwann cells to the wall of the third arch artery. The third arch artery provides mesenchymal cells, which give rise to sustentacular cells. The nerve process from the SCG sends glomus cell progenitors into the carotid body primordium. The presence of stem cells in the adult carotid body was recently highlighted. The origin of stem cells, however, remains controversial. Based on embryonic development of the carotid body, this review proposes the origin of stem cells. Key Findings: Three elements are required for carotid body organization; carotid sinus nerve (CSN), third arch artery, and superior cervical sympathetic ganglion (SCG). First, the CSN supplies the sensory fibers to the third arch artery. Then, the carotid body primordium is formed in the wall of the third arch artery in which mesenchymal cells differentiate to sustentacular cells. The SCG sends glomus cell progenitors into the carotid body primordium. The genes involved in development of the three elements have been highlighted.